How far climate change affects the Indonesian paddy production and rice price volatility? - Silvia Sari Busnita, Rina Oktaviani, Tanti Novianti (Universitas Andalas, 2017)
Food security issue after 2008 global-crisis is something relate with the climate change phenomenon which had worsened on the last few decades. The impact of global climate change can be seen from the fluctuation of main crops production yield in tropical countries. This has affected the food price fluctuations particularly on the grain price, both international and domestic markets. The rice-commodity, known for its thin market characteristics, is now also experiencing the fluctuation of production, its productivity and also the rice price. Considering the importance of rice as the main staple food in Indonesia, the purpose of this research is to identify the Indonesia’s rice price fluctuation (volatility) and to investigate how far climate change affects the Indonesian paddy production and rice price volatility. By applying monthly time-series data from 2007 to 2014, this research used ARCH-GARCH methods to find out the rice price volatility and VECM (Vector Error Correction Model) to investigate the impact of climate change phenomenon on the Indonesian paddy production, as well as rice price volatility both in the short-run and long-run. The result is important for the stakeholders and government in preventing the risk and uncertainty condition of paddy production and rice price fluctuation caused by climate change